Field Performance of Rhizobial Inoculants on Lentil - Bhuiyan, M Asadul Haque; Khanam, Delowara; Ali, M Eyakub; Alam, Fardul; Rahman, M Arifur (Bangladesh Journal of Microbiology, 2011)
A field experiment was conducted at Regional Agricultural Research Station (RARS), Jamalpur during rabi season of 2005-2006 and 2006-2007 to find out the effectiveness of Rhizobium strains on lentil. BARI Masur– 4 and Rhizobium inoculum (strains BARI RLc-104, BARI RLc-105, BARI RLc-106 and BARI RLc-107) were used in this experiment. Unit plot size was 4 m x 3 m. The experiment was designed in randomized complete block having 4 replications for each treatment. There were six treatments, T1: Rhizobium strain BARI RLc- 104, T2: Rhizobium strain BARI RLc-105, T3: Rhizobium strain BARI RLc-106, T4: Rhizobium strain BARI RLc– 107, T5: mixed culture of the above four strains and T6: control. The strains were used to prepare peat based rhizobial inocula which were used @ 1.5 kg ha-1. A basal dose of P, K, S, Zn @ 22, 42, 20, 5 kg ha-1, respectively for all treatments were used in the experiment. Plant receiving peat based rhizobial inocula (strain BARI RLc-104, BARI RLc-105, BARI RLc-106, BARI RLc-107 and mixed culture) produced significantly higher nodule number, nodule weight, stover yield and seed yield over non-inoculated control. The highest nodule number (12.84 plant-1 in 2006 and 12.30 plant-1 in 2007) and nodule weight (10.51 mg plant-1 in 2006 and 13.53 mg plant-1 in 2007) were found with strain BARI RLc-104. This strain also recorded the highest seed yield (1.23 t ha-1, 55.7% higher over non-inoculated control) in 2006 but BARI RLc-107 produced the highest seed yield (1.20 t ha-1, 50.0% higher over non-inoculated control) in 2007 though all the strains including mixed culture recorded identical yields. Key words: Rhizobium; lentil, nodulation; yield DOI: http://dx.doi.org/10.3329/bjm.v27i1.9163 BJM 2010; 27(1): 18-21